Individual happiness and well-being as a strategy to increase productivity - Pratiwi, Awalya Siska; Setiyowati, Arbin Janu (Research and Social Study Institute, 2024)
This research aims to examine the role of happiness and well-being as key factors in enhancing individual productivity. With the growing body of research on mental health and well-being, a new understanding has emerged regarding the strong connection between emotional well-being and productive performance. Through a literature review, this study identifies and analyzes various empirical studies that explore the impact of happiness and well-being on productivity in different contexts, both in the workplace and in everyday life. The review process employed a systematic literature review method, with inclusion criteria encompassing studies published within the last four years and written in English or Indonesian. The findings indicate that happiness and well-being not only contribute to improved performance but also play a pivotal role in fostering an environment that supports sustainable productivity growth.